2020
DOI: 10.1542/hpeds.2019-0286
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Pediatric Residents’ Social Needs Screening Practices Across Health Care Settings

Abstract: The American Academy of Pediatrics recommends that all pediatricians screen for social determinants of health to identify families in need and connect them to available resources. We examined pediatric residents' screening practices for social needs in different clinical settings and explored the influence of electronic health record (EHR) prompts on screening. METHODS:In this cross-sectional study, pediatric residents participated in a brief electronic survey assessing (1) screening practices for unmet social… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…A recent systematic review by Quiñones-Rivera and colleagues [19] found that providers held generally positive attitudes and beliefs about the importance of addressing social needs, however, they identified barriers to social needs screening including concerns regarding patient discomfort at being questioned, increasing pressure on time and workflow, risk to patient-provider relationships, and a lack of knowledge about how to address identified social needs [19]. A number of studies focused on the readiness of doctors and nurses in primary healthcare settings [3,17,[26][27][28]. One study identified disparities in screening rates between healthcare providers in the outpatient and inpatient settings, finding that a greater proportion of paediatric residents screened for social needs in the outpatient setting compared to those in the inpatient setting [28].Interestingly, paediatric residents cited the same barriers (time constraints, lack of knowledge, perceived patient discomfort) in both outpatient and inpatient settings [28].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent systematic review by Quiñones-Rivera and colleagues [19] found that providers held generally positive attitudes and beliefs about the importance of addressing social needs, however, they identified barriers to social needs screening including concerns regarding patient discomfort at being questioned, increasing pressure on time and workflow, risk to patient-provider relationships, and a lack of knowledge about how to address identified social needs [19]. A number of studies focused on the readiness of doctors and nurses in primary healthcare settings [3,17,[26][27][28]. One study identified disparities in screening rates between healthcare providers in the outpatient and inpatient settings, finding that a greater proportion of paediatric residents screened for social needs in the outpatient setting compared to those in the inpatient setting [28].Interestingly, paediatric residents cited the same barriers (time constraints, lack of knowledge, perceived patient discomfort) in both outpatient and inpatient settings [28].…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies focused on the readiness of doctors and nurses in primary healthcare settings [3,17,[26][27][28]. One study identified disparities in screening rates between healthcare providers in the outpatient and inpatient settings, finding that a greater proportion of paediatric residents screened for social needs in the outpatient setting compared to those in the inpatient setting [28].Interestingly, paediatric residents cited the same barriers (time constraints, lack of knowledge, perceived patient discomfort) in both outpatient and inpatient settings [28].…”
Section: Introductionmentioning
confidence: 99%
“…Studies targeted a diverse range of populations. For example, children were the focus in some studies [32,36], while adults were the primary subjects in studies [33,37]. Various healthcare settings were represented, from primary care clinics [38,39] to emergency departments [40], as well as school-based clinics [34] indicating the widespread recognition of the importance of SDoH in different medical environments, underscoring the growing acknowledgment of SDoH’s relevance across the healthcare spectrum.…”
Section: Resultsmentioning
confidence: 99%
“…Integration of these questionnaires would allow structured EHR documentation of patient SDoH with minimal impact on patient burden and clinical workload. Participants also suggested embedding the SDoH module items in existing well-child encounter note templates, a method that has shown success in other settings [17,47]. While these strategies are promising, the deployment of these modifications requires leadership buy-in, healthcare system prioritization, and information technology (IT) resource allocation.…”
Section: Discussionmentioning
confidence: 99%